Methodological Approaches to Assessing the Condition and Management of Young River Landscapes under the Conditions of Anthropogenic River Incision (Ukrainian Carpathians) - Zaiachuk, M. D.; Yushchenko, Yu. S.; Pasichnyk, M. D.; Palanychko, O. V.; Nastiuk, M. H. (Ukrainian Geographical Journal, 2025)
River cutting is among the most important processes of river sites’ anthropogenic transformations. Such processes are often and largely due to the extraction of channel alluvium, which sometimes represents said transformations’ major factor within many river reaches. A complex study of rivers’ anthropogenic cutting was carried out within a system of measures to help improve the quality of river ecosystems and sites. The study aims to disclose the importance of considering the river’s anthropogenic cutting while planning to manage river site quality and present recommendations to solve the problem. We have used the identification methods of natural young river sites, complex methods of identification and monitoring of anthropogenic cutting, and the analysis of cutting consequences together with the assessment of the current state of such sites in current conditions concerning their hydro-morphological parameters. Problems of anthropogenic cutting in river management planning in Ukraine were analyzed. Characteristic examples of the rivers of Prut, Siret, and Cheremosh within the limits of the Chernivtsi Oblast were discussed. It was proved that cutting intensity makes 100–200 mm/year. The cutting results in a concentration of channel flow, changes in the channel process, changes in the functioning of floodplains, danger for engineering constructions, etc. High-intensity and significant-amplitude cuttings mean that the state of the river site, according to its hydro-morphological parameters, is referred to as “bad,” and the humans essentially transform the site itself. All these issues should be considered in management planning. The study presents respective recommendations.
Keywords: site planning; river basin management planning; anthropogenic cutting of rivers; channel regulation; young river site; river site state and quality; hydro-morphological parameters of quality